2018
DOI: 10.33886/mj.v1i1.60
|View full text |Cite
|
Sign up to set email alerts
|

Tutor ICT Skills and the Realisation of Kenya’s Vision 2030

Abstract: The Kenya Vision 2030 identifies science, technology and innovation as key drivers in creating wealth, social welfare and international competitiveness. In recognition of the role of technology in achieving Vision 2030, the government pledged to strengthen technical capabilities by emphasising technological learning at all levels. The vision affirmed that it is only through an educated and skilled manpower that Kenya will be able to create, share and utilise knowledge well. To produce a workforce capable of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research has shown that the selfconfidence and competence of teachers affected their using technology in instruction (Peralta and Costa, 2007;Oral, 2008). It has also shown that tutors were not good models on the use of technology in teacher training, and did not require students to use technology (Mukuna, 2013;Muyaka & Gathara, 2013). It is common knowledge that the skills that we invest in the teachers get replicated among students while they teach.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the selfconfidence and competence of teachers affected their using technology in instruction (Peralta and Costa, 2007;Oral, 2008). It has also shown that tutors were not good models on the use of technology in teacher training, and did not require students to use technology (Mukuna, 2013;Muyaka & Gathara, 2013). It is common knowledge that the skills that we invest in the teachers get replicated among students while they teach.…”
Section: Introductionmentioning
confidence: 99%